Developing Science Edutainment for Prospective Science Teachers - Prasetyaningsih, ‎; Liliasari, ‎; Ramlan Ramalis, Taufik; Septem Riza, Lala (KnE Social Sciences, 2024)
Providing public knowledge about disasters can be done through integrated learning in science. This study aimed to determine the various needs for implementing science edutainment for science prospective science teachers. This study was a qualitative descriptive research. The subjects of the research were two lecturers who teach Disaster Mitigation courses and 67 students prospective science teachers in Banten who received lectures on Disaster Mitigation and BPBD Banten. Data was collected using non-test instruments through document analysis, questionnaires, and interviews, as well as qualitative descriptions for data analysis. With regard to various needs in the implementation of science edutainment disaster, the results showed the implementation of disaster education needs to be developed, especially involving relevant agencies such as BPBD to develop the empirical experience of prospective science teachers. Additionally, it needs to be integrated with practicum using modules by utilizing technology used in socialization and disaster risk management. Development of Disaster Mitigation modules needs to be carried out, especially modules that improve natural disaster literacy critical and creative thinking skills of prospective science teachers. Keywords: Science Edutainment, Prospective, Science Teachers